Modification of chitosan with carbamoyl benzoic acids for testing its coagulant-flocculant and binding capacities in removal of metallic ions typically contained in plating wastewater - Martinez Quiroz, Marisela; López Maldonado, Eduardo Alberto; Ocho-Terán, Adrián; Pina-Luis, Georgina; Oropeza-Guzmán, Mercedes T. (My University, 2017)
This paper proposes the use chitosan modified with carbamoyl benzoic acids as new coagulant-flocculant agents for metals removal from aqueous solutions. The grafted chitosan species as chitosan dianhydride (ChD) and chitosan dianhydride-amine (ChDA) improved the removal of Cu2+, Pb2+, Ca2+, Cr3+, Zn2+ and Ni2+, compared with chitosan alone. Zeta potential measurements predict doses and allowed to calculate binding constants between the new coagulant-flocculant agents and metallic cations (from 104 to 105 M−1). After the coagulationflocculation, solids were analyzed by SEM and EDS. SEM images show the texture of solids depending on the functional group grafted on chitosan. EDS study of solids containing chitosan dianhydride-metals (average of all scanner areas) revealed the wt% of metals: Cr (10.45%), Cu (5.95%), Ni (5.22%), Zn (4.36%), Pb (1.37%), Cd (0.31%) and Ca (0.10%) For recovered solids containing chitosan dianhydride-amine-metals, the observed wt% appeared in the same order: Cr (12.44%), Cu (6.75%), Ni (5.75%), Zn (5.12%), Pb (1.82%), Cd (0.59%) and Ca (0.12%).
Chemical Engineering Journal
Keywords: Modified chitosan; Carbamoyl benzoic acid; Grafting molecules; Coagulation-flocculation kinetics; Metals removal